2005
DOI: 10.1152/ajpregu.00469.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of disuse muscle atrophy: role of oxidative stress

Abstract: Prolonged periods of skeletal muscle inactivity lead to a loss of muscle protein and strength. Advances in cell biology have progressed our understanding of those factors that contribute to muscle atrophy. To this end, abundant evidence implicates oxidative stress as a potential regulator of proteolytic pathways leading to muscle atrophy during periods of prolonged disuse. This review will address the role of reactive oxygen species and oxidative stress as potential contributors to the process of disuse-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
282
2
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 316 publications
(296 citation statements)
references
References 60 publications
(99 reference statements)
7
282
2
5
Order By: Relevance
“…Muscle wasting in the above‐mentioned conditions also involves ROS production, which has been found to be associated with protein catabolism and ubiquitin‐proteasome pathway (Li & Reid, 2000; Gomes‐Marcondes & Tisdale, 2002). In addition, oxidative stress during aging is considered to be a major contributor of muscle atrophy (Sohal & Weindruch, 1996; Powers et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle wasting in the above‐mentioned conditions also involves ROS production, which has been found to be associated with protein catabolism and ubiquitin‐proteasome pathway (Li & Reid, 2000; Gomes‐Marcondes & Tisdale, 2002). In addition, oxidative stress during aging is considered to be a major contributor of muscle atrophy (Sohal & Weindruch, 1996; Powers et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an increase in reactive oxygen species (ROS) in muscle in response to infection, inflammatory stimulus and/or aging (Sohal & Weindruch, 1996; Powers et al. , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in mitochondrialdependent and mitochondrial-independent mediated apoptosis, caspase-3 also serves as a protease involved in myofibrillar protein release, resulting in contractile protein proteolysis (10). Therefore, inhibition of caspase-3 during MV may result in the retardation of myofilament release associated with myofiber atrophy in this model.…”
Section: Mv-induced Myonuclear Apoptosismentioning
confidence: 91%
“…In addition to myofibrillar protein loss, extracellular matrix expansion, and metabolic enzyme alterations (9)(10)(11), prolonged disuse of skeletal muscle results in the selective loss of myonuclei (12)(13)(14)(15)(16). Myonuclear loss may be a strategy used by the fiber to maintain a constant ratio of cytoplasmic myofiber volume per myonucleus (i.e., myonuclear domain) (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation